The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1111/1475-4932.t01-1-00097
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Capacity Constraints in Australian Manufacturing Industry

Abstract: In the present paper we estimate a model of price-cost inflation for Australia using business survey responses of firms in the manufacturing sector. The data allow us to circumvent a number of key statistical problems, related in particular to the measurement of costs and structural changes in the model. Equally important, the data allow a new and more detailed perspective on the nature of supply constraints affecting inflation in the manufacturing sector. A new finding is that capital constraints have been mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…There remains some debate concerning the appropriateness of the unemployment rate as a measure of labour market tightness. For example, Shepherd and Driver (2003) used a range of survey‐based measures of supply capacity conditions for both labour and capital, whereas Ghua and Visviki (2001) found that employment growth in non‐farm payrolls is a better measure of labour market tightness in the USA. Unemployment, however, is commonly used for this purpose and has therefore been maintained in this application.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…There remains some debate concerning the appropriateness of the unemployment rate as a measure of labour market tightness. For example, Shepherd and Driver (2003) used a range of survey‐based measures of supply capacity conditions for both labour and capital, whereas Ghua and Visviki (2001) found that employment growth in non‐farm payrolls is a better measure of labour market tightness in the USA. Unemployment, however, is commonly used for this purpose and has therefore been maintained in this application.…”
Section: Theoretical Modelmentioning
confidence: 99%